2017
DOI: 10.1007/s13204-017-0570-2
|View full text |Cite
|
Sign up to set email alerts
|

DNA–carbon nano onion aggregate: triangle, hexagon, six-petal flower to dead-end network

Abstract: The interaction between calf-thymus (CT) dsDNA and water soluble carbon nano onion (wsCNO) in water follows denaturation of dsDNA (double stranded) to ssDNA (single stranded) as monitored by optical spectroscopy. The ssDNA concomitantly wraps the spiky surface of wsCNO to create triangular aggregate as the building block as observed by time-dependent SEM images. These triangles further aggregate leading to six-petal flower arrangement via hexagon and finally reach a dead end network as imaged by SEM and optica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“… 19 , 20 Also the denaturation and deactivation of ds-DNA under similar light-induced interaction with CNO were reported. 24 Therefore, the mode of action of hydrogen peroxide to destroy SARS-CoV-2 may be envisioned as follows. The lipid layer of SARS-CoV-2 has several pockets to invite hydrogen bond interactions with hydrophilic CNO leading to adduct formation.…”
Section: Resultsmentioning
confidence: 99%
“… 19 , 20 Also the denaturation and deactivation of ds-DNA under similar light-induced interaction with CNO were reported. 24 Therefore, the mode of action of hydrogen peroxide to destroy SARS-CoV-2 may be envisioned as follows. The lipid layer of SARS-CoV-2 has several pockets to invite hydrogen bond interactions with hydrophilic CNO leading to adduct formation.…”
Section: Resultsmentioning
confidence: 99%
“…49,75 The first supramolecular CNO-based system was reported 2008, by Echegoyen et al 76 Since then, non-covalent binding has become increasingly popular as a mode of moiety-attachment to the CNO surface. 29,49,50,[77][78][79][80][81][82][83][84][85][86] Moreover, in the recent years, an increasing interest has been observed in utilising non-covalent functionalisation for drug delivery related applications. 37,38 As the primary function of a nanocarrier is to deliver and release a drug payload at the target site, one must consider an appropriate approach for appending the drug onto the nanomaterial surface.…”
Section: Modification Of the Nanocarriermentioning
confidence: 99%
“…This dead-end network aggregate lacked the intrinsic optical property of DNA and displayed a loss of its activity (Figure 10). The researchers finally concluded that the wsCNO being non-toxic can be explored to control the unwanted proliferation of rouged DNA by interacting with wsCNO, which can be utilized for the prevention of such viral DNA replication in recognized diseases [200]. Tripathi et al developed graphitic photoluminescent water-soluble carbon nanoonions (wsCNO) from the traditional pyrolysis of vegetable ghee without employing any metal catalyst through a simple oxidative treatment using nitric acid.…”
Section: Carbon Nano-onions For Therapeutics Deliverymentioning
confidence: 99%